IbM PUSAT KEGIATAN BELAJAR MASYARAKAT - PKBM [IbM CENTER OF COMMUNITY LEARNING] - Ema Utami; Suyatmi Suyatmi (Universitas Pelita Harapan, 2017)
One of government efforts to deliver educational equity in society is conduct education equality program. Center of community learning (PKBM), an institution created by community or society that having management principle: by, from and for society. Two PKBM named P. Diponegoro and Bangunmulya are example of PKBM in Sleman District. Main problems faced by P Diponeforo and Bangunmulya PKBM are lacked of tutor or trainer to teaching life skills for student in PKBM even though life skills are important materials in addition to formal knowledge. The considerations why PKBM should teach life skill for student because they are easy to learn, less funding, short time to learn and marketable. The offer solutions for faced problems are conduct training activities such as : 1) utilization computer as aids to create and design creative products having economic value; 2) using of graphic design software to create and design mugs and pins cover; 3) Optimization Internet as promotion media; 4) Increasing entrepreneurial spirit in Internet Era; 5) Management and utilization of PKBM website. In addition to life skill training, PKBM website is developed to be information and promotion media for product made by PKBM students also as communication media between administrator, students and society. The outcome form this program are : 1) increase of student knowledge about informatics roles to create and design economic value products; 2) Bangunmulya PKBM students able to using CorelDraw software for create and design batik graphics and print it into mug media using sublime printer; 3)P Diponegoro PKBM students able to using CorelDraw software for create and design graphics and print it using printer press machine; 5) PKBM students are inspired from successful entrepreneurs that using web and social media in the business; and 6) availability of website as promotion and communication media between management, students and society.